2007
DOI: 10.3748/wjg.v13.i38.5147
|View full text |Cite
|
Sign up to set email alerts
|

Wilson disease: Identification of two novel mutations and clinical correlation in Eastern Chinese patients

Abstract: AIM:To study mutations in the P-type ATPase (ATP7B) gene responsible for Wilson disease (WD) in the Eastern Chinese population, and the possible correlation of specific mutations with clinical characteristics. METHODS:Mutations of the ATP7B gene were sought by means of direct sequencing in 50 Eastern Chinese WD patients of Han ethnic origin. RESULTS:Tw o n o v e l m u t a t i o n s , A s p 9 6 G l y a n d Asp196Glu, were first identified. We also compared the characterization of mutations in ATP7B with the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…No significant difference was found in the levels of serum copper or ceruloplasmin in these two groups. We observed that the average onset age in compound heterozygotes was significantly earlier (P¼0.002) than that in the homozygotes, which is in contradiction to the findings reported by Ye et al 13 and Wu et al 23 This difference might be because the patient groups in the different studies were from different geographic areas of China and there are only two homozygotes in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…No significant difference was found in the levels of serum copper or ceruloplasmin in these two groups. We observed that the average onset age in compound heterozygotes was significantly earlier (P¼0.002) than that in the homozygotes, which is in contradiction to the findings reported by Ye et al 13 and Wu et al 23 This difference might be because the patient groups in the different studies were from different geographic areas of China and there are only two homozygotes in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…The p.Arg778Leu mutation was the most frequent in our patients, accounting for 23.29% of alleles studied. It is the most prevalent mutation in other Chinese populations, such as eastern Chinese (50%) 13 and Taiwanese (27%). 14 It is also the most common mutation in Asian populations, including Korean (37.9%), 15 Japanese (13.4%) 16 and Thai (10.52%).…”
Section: Discussionmentioning
confidence: 99%
“…Position 778 has a high frequency of mutation among Taiwanese patients, between 27% and 43.1% 1, 2, 12, 13. According to several reports, the c.−75A→C substitution in the promoter region may be a single‐nucleotide polymorphism 2, 18‐20. We also identified this single‐nucleotide polymorphism in the control subjects with a minor allele frequency of 35.5%.…”
Section: Discussionmentioning
confidence: 64%
“…It would also be important to see if the phenotypes associated with a particular mutation of ATP7B gene in WD within families are the same as in WD patients with the same mutations, but in a different family or a different population [19] . Application of a standard phenotypic classification like the international consensus phenotypic classification for WD [8] in future studies will enable valid comparison of the results.…”
Section: Discussionmentioning
confidence: 99%